1997
DOI: 10.1037/0022-0663.89.4.728
|View full text |Cite
|
Sign up to set email alerts
|

Race and academic disidentification.

Abstract: This issue compleles Volume 89 and contains the author index for the volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
247
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(263 citation statements)
references
References 28 publications
12
247
1
3
Order By: Relevance
“…Girls appear to have a general advantage in overall school success, across African-American and other ethnicities, as well as both disadvantaged and non-disadvantaged adolescents (De Bruyn et al, 2003;Osborne, 1997). However, findings on the role of gender in the relation between family process and school success are not as clear.…”
Section: Introductionmentioning
confidence: 67%
“…Girls appear to have a general advantage in overall school success, across African-American and other ethnicities, as well as both disadvantaged and non-disadvantaged adolescents (De Bruyn et al, 2003;Osborne, 1997). However, findings on the role of gender in the relation between family process and school success are not as clear.…”
Section: Introductionmentioning
confidence: 67%
“…It is expected that students who experience repeated academic failure are likely to develop negative feelings about themselves, on the contrary, those who encounter success tend to develop positive views of themselves. It has often been suggested that academic achievement is closely related to self-esteem (Osborne, 1997;Pullmann & Allik, 2008;Suk Wai Wong & Watkins, 2001;Stupniskyet, Renaud, Perry, Ruthig, Haynes, & Clifton, 2007;Whitesell, Mitchell, & Spicer, 2009), nevertheless, considering the literature, this relationship is more complicated than it is thought to be. Some researchers asserted that self-esteem affects academic achievement (Chapman, 1988;Hansford & Hattie, 1982;Marsh, Byrne, & Shavelson, 1988), however some others claim it is affected by academic achievement (Alves-Martinset, Peixoto, Gouveia-Pereira, Amaral, & Pedro, 2002;Baumeister, Campbell, Krueger, & Vohs, 2003;Bowles, 1999;Filozof, Albertin, Jones, Steme, Myers, & McDermott, 1998;Hoge, Smit, & Crist, 1995).…”
Section: Self-esteem and Academic Achievementmentioning
confidence: 76%
“…Despite the limited number of studies specifically addressing school racial climate among high school youth, a growing body of theory and research on various aspects of secondary schooling suggests that matters of race may affect students' experiences in schools and deserve attention (e.g., Aronson et al, 1998;Ogbu, 1978Ogbu, , 1994Mickelson, 1990;Steele, 1992Steele, , 1995Steele, , 1997Osborne, 1995Osborne, , 1997Steele & Aronson, 1995).…”
Section: Racial Climate and Schoolingmentioning
confidence: 99%